Media Wars and Public Diplomacy - Kishan Thussu, Daya (Javnost-The Public, 2000)
This article examines the dynamics between Western public diplomacy and the mediation of international military conflicts by US-dominated global television news. It looks at aspects of television coverage of wars in the post-Cold War era, in particular the 1999 Kosovo crisis and argues that only the wars in which the West has a geo-strategic interest appear to receive adequate coverage by Western television. NATO's bombing of Yugoslavia in March-June 1999 was the most extensively covered military action since the 1991 Gulf War. In both cases, Western television news channels, notably Cable News Network (CNN), consistently reproduced the agenda set by the United States and moulded public opinion in support of war. NATO's campaign in Kosovo was represented as a "humanitarian" involvement instead of it being an action aimed at establishing a precedent for intervention into the internal affairs of a sovereign state and outside its area of operation. The article assesses international implications of such coverage, arguing that given the global reach and influence of Western television and the dependence of world's broadcasters on US-supplied television news footage, the dominant perspectives on a conflict can be American, although the US, more often than not, may be actively involved in the war. Recognising this, the article argues, that Western diplomacy has become sophisticated in packaging public information in a visually astute fashion and television networks, which often operate in a symbiotic relationship with the authorities, tend to conform to the geo-political agendas set by powerful governments.